The administrative compensation system for pollution-related health damages in Japan: Overview and preliminary evaluation - Helmut Weidner (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1989)
Japan is the only country in the world that has an extensive, specially regulated compensation system for diseases considered to have resulted from environmental pollution. For certain types of diseases, the system provides for financial compensation and other benefits prorated according to the severity of the case. Much of this compensation is paid by the firms responsible for pollution in the first place, while an automobile tax is collected to cover some of the costs in cases involving air pollution. Certain costs (for administration and rehabilitation progams, for example) are assumed in whole or in part by public funds. The compensation in its present form was created by the Pollution-Related Health Damage Compensation Law of 1973, which took effect in 1974. In March 1988, through an amendment of the law, the compensation system was fundamentally revised. The paper describes in detail the organisation and functioning of the system as well as its shortcomings as perceived by Japanese experts.
Keywords: 320